'Natural' progesterone creams for postmenopausal women. Issue 2 (1st February 2001) - Unknown
Abstract : Creams containing 'natural' progesterone for application to the skin have been available over the counter in mainland Europe and the USA for around 20 years. They are not licensed in the UK and their availability here (in the form of Pro-Gest or Pro-Juven creams, all distributed by Higher Nature) is limited to provision by prescription on a named-patient basis (related formulations are also being purchased from abroad by mail-order and via the Internet). Their UK distributor claims the creams can help treat menopausal symptoms and may prove useful in the prevention and treatment of osteoporosis in postmenopausal women.1 Here, we assess the efficacy and safety of 'natural' progesterone creams in the treatment of postmenopausal symptoms. In particular, we look at whether the products can protect against osteoporosis, or adequately oppose stimulation of the endometrium by exogenous oestrogen and so replace the progestogen component of conventional HRT.